ANALISIS INDEKS PEMBANGUNAN MANUSIA PROVINSI JAWA TENGAH MENGGUNAKAN ANALISIS REGRESI - Fawwaz Ziddan Azis; Triyani Hendrawati; Azmi Muhammad Nafis; Dimas Fattah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The Human Development Index is one approach to measuring the success rate of human development. Central Java Province is one of the provinces that experienced an increase in the human development index in 2022. Therefore, this study was conducted to determine the regression model used and the factors that affect the human development index in Central Java Province in 2022. Some of the factors used in this study are life expectancy, average years of schooling, expected years of schooling and adjusted per capita expenditure. The method used in this research is multiple linear analysis, parameter significance test, and classical assumption test. By using the human development index as the response variable (Y), life expectancy (X1), average years of schooling (X2), expected years of schooling (X3) and adjusted per capita expenditure (X4) as predictor variables. From the results of the analysis that has been done, the equation Y = 6.55 + 0.4626X₁ + 1.341X₂ + 0.8971X₃ + 0.0008329X₄ +e is obtained. This shows that there is a relationship between the human development index and life expectancy, average years of schooling, expected years of schooling and adjusted per capita expenditure. The classical assumption test, namely the normality test, multicollinearity test, autocorrelation test and heteroscedasticity test, shows that the regression model can be used